Dictionary of Latin and Greek theological terms : drawn principally from Protestant scholastic theology - Muller, Richard A. 1948- (Baker Academic, 2017)
This indispensable companion to key post-Reformation theological texts provides clear and concise definitions of Latin and Greek terms for students at a variety of levels. Written by a leading scholar of the Reformation and post-Reformation eras, this volume offers definitions that bear the mark of expert judgment and precision. The second edition includes new material and has been updated and revised throughout.